2014
DOI: 10.3171/2014.8.gks141506
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for vestibular schwannoma: clinical results at long-term follow-up in a series of 379 patients

Abstract: ObjectSince the 1990s, Gamma Knife radiosurgery (GKRS) has become the first-line treatment option for small- to medium-size vestibular schwannomas (VSs), especially in patients without mass effect–related symptoms and with functional hearing. The aim of this study was to assess the safety and efficacy of GKRS, in terms of tumor control, hearing preservation, and complications, in a series of 379 consecutive patients treated for VS.MethodsOf 523 patients treated at the authors' institution for VS between 2001 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 66 publications
13
132
0
1
Order By: Relevance
“…Despite a good clinical outcome, new CNs deficit have been reported even after Gamma Knife radiosurgery for glomus tumor. 44 A prescription dose ≤13 Gy showed low risk of vertigo, facial impairment, and trigeminal neuralgia after Gamma Knife radiosurgery for vestibular schwannomas, and the probability of developing trigeminal neuralgia was strictly related to the volume of brainstem exposed to a dose of 10 Gy. 32,40,41 Other less frequent reported cranial neuropathies after Gamma Knife radiosurgery are trigeminal neuralgia and facial weakness.…”
Section: Discussionmentioning
confidence: 89%
“…Despite a good clinical outcome, new CNs deficit have been reported even after Gamma Knife radiosurgery for glomus tumor. 44 A prescription dose ≤13 Gy showed low risk of vertigo, facial impairment, and trigeminal neuralgia after Gamma Knife radiosurgery for vestibular schwannomas, and the probability of developing trigeminal neuralgia was strictly related to the volume of brainstem exposed to a dose of 10 Gy. 32,40,41 Other less frequent reported cranial neuropathies after Gamma Knife radiosurgery are trigeminal neuralgia and facial weakness.…”
Section: Discussionmentioning
confidence: 89%
“…The initial review could discard 997 records as not relevant to the topic or as inadequate regarding cohort size or follow-up time, and after reference cross-check 98 records were reviewed according to a systematic review protocol. After the second review round a final 19 records were found to fulfill all inclusion criteria [2, 6, 10, 15, 17, 19, 22, 24, 28, 29, 33, 36, 39, 44, 48, 50, 52, 53, 56]. No randomized studies (S1) were identified on the subject.…”
Section: Resultsmentioning
confidence: 99%
“…In another study of 100 patients aged 65 or older (median age 71 years) treated with FSRT (56.5 Gy), hypofractionated stereotactic RT (36.3 Gy in 5–7 fractions) or single-fraction SRS (17.6 Gy), Kaul et al [123] observed a 5-year local control of 91.1%, with no grade 2 or 3 neurological toxicity. No study have specifically addressed the outcome of RT in older patients with either secreting or nonsecreting pituitary adenomas, and acoustic neuromas; however, data reported in large retrospective studies and systematic reviews show similar local control and toxicity between young and older patients after either SRS or FSRT [124142]. Single-fractions doses of 13–16 Gy and 20–28 Gy are usually employed for non-functioning and secreting pituitary adenomas [124, 125, 129134], respectively, and of 12–14 Gy for acoustic neuromas [135, 137, 139142].…”
Section: Benign Tumorsmentioning
confidence: 99%
“…No study have specifically addressed the outcome of RT in older patients with either secreting or nonsecreting pituitary adenomas, and acoustic neuromas; however, data reported in large retrospective studies and systematic reviews show similar local control and toxicity between young and older patients after either SRS or FSRT [124142]. Single-fractions doses of 13–16 Gy and 20–28 Gy are usually employed for non-functioning and secreting pituitary adenomas [124, 125, 129134], respectively, and of 12–14 Gy for acoustic neuromas [135, 137, 139142]. Hypofractionated RT and FSRT using doses of 21–25 Gy in 3–5 fractions and 45–54 Gy in 25–30 daily fractions of 1.8 Gy, respectively, are frequently employed for large tumors involving the optic pathway or compressing the brainstem [126128, 133136, 138].…”
Section: Benign Tumorsmentioning
confidence: 99%